Picture of participants of the training workshop on Water Accounting Plus Tool held in Egypt from 5th to 7th December 2022 - Brouziyne, Youssef (2023)
Picture of participants of the training workshop on Water Accounting Plus Tool held in Egypt from 5th to 7th December 2022